Pilgrimage as Third Space: Contesting Image of Sunan Ampel - Achmad Fawaid (Proceedings of Annual Conference for Muslim Scholars, 2017)
This paper is to analyze â€œimageâ€ of Sunan Ampel, including Ampel tombs, mosque, wells, and market, projected within the three online directoriesand the possible impacts of this use on different visitors. By using Turnerâ€™s concept â€œcommunitasâ€, liminality, and third space, Sunan Ampel site is also considered as a space in which the ties between tourism and pilgrimage are unclear, blurred, and poorly classified. This relationship has also resulted in possible potentialities on how that site has projected mysticism, death, and apophantic nature of Sunan Ampel. The changing projection of the site will be also highlighted in the context of economic and social contestation. The consequence of such interpretation is that Sunan Ampel could be empty vessel in which the interpretative battle and representations are continuosly contested. â€œSacred pilgrimageâ€ to Sunan Ampel, finally, overlaps with tourism, trade, expression of nationalism, cyber-pilgrimage, and others.